FROM SCRIPT TO SPEECH: THE INTERPLAY BETWEEN WRITTEN AND ORAL TRADITIONS IN PHILOLOGICAL STUDIES - Khilola Ismoilova,; Robiya Ismonaliyeva,; Mohlaroy Qodirova, (TADQIQOTLAR, 2025)
The dynamic relationship between written and oral traditions has long intrigued philologists,  as  both  forms  of  expression  reveal  the  evolution  of  human  language, culture, and cognition. This study examines the interplay between script and speech within philological research, highlighting how oral traditions influence written texts and how literacy transforms oral expression. Drawing from classical, medieval, and indigenous  linguistic  traditions,  the  article  explores  how  oral  performance, memorization, and storytelling shaped the transmission of texts before and after the advent of writing. The research also addresses how modern philology, supported by linguistic anthropology and digital humanities, redefines the boundaries between oral and written forms. Case studies from Homeric epics, Old English poetry, and African oral  literature  demonstrate  that  script  and  speech  are  not  opposing  systems  but complementary forces in cultural preservation. The paper concludes that philological inquiry into both forms deepens our understanding of linguistic creativity and cultural continuity.